Evaluation of soluble transferring receptor levels in children with iron deficiency and beta thalassemia trait, and in newborns and their mothers - Polat, Aziz; Kaptanoğlu, Bünyamin; Aydın, Kemal; Keskin, Ali (The Turkish Journal of Pediatrics, 2002)
In this study we first aimed to investigate the value of soluble transferrin receptor levels (sTfR) in healthy, iron deficient and beta thalassemia trait children and to determine whether sTfR is a useful indicator of iron deficiency. Secondly, we investigated the effects of iron supplementation of sTfR levels in a group of iron deficient children. Third was to describe sTfR in newborn infants and determine whether or not maternal iron deficiency is an important predictor of infant sTfR. Six groups were formed: Children with iron deficiency (n=22), post-iron therapy (n=16), beta thalassemia traits (n=19), healthy children (n=19), full-term newborns (n=20), and their mothers (n=19), Complete blood count (CBC), serum iron, iron-binding capacity, ferritin and sTfR levels were measured. sTfR/log ferritin indexes were calculated. sTfR levels of children with iron deficiency and with beta thalassemia trait were found to be significantly higher than those of healthy children (p
Keywords: soluble transferring receptor; iron deficiency; beta thalassemia trait; newborn; children